Inventory and quality control of biosample collection from pregnant women at different gestational ages to search for early biomarkers of pregnancy complications - A. R. Maltseva; R. A. Illarionov; E. S. Vashukova; O. V. Pachulia; T. B. Postnikova; M. E. Velizhanina; A. A. Rubel; Yu. A. Nasykhova; O. N. Bespalova; A. S. Glotov (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To conduct an inventory and quality control of biosample collection from pregnant women at different gestational ages to search for early biomarkers of pregnancy complications.Material and methods. In this work, methods for assessing the sample preparation of biosamples were used, including the isolation of deoxyribonucleic acid (DNA)/ribonucleic acid from various biomaterials, polyacrylamide gel electrophoresis of protein, and database analysis.Results. Inventory and quality control of the collection (n=18390) was carried out, which confirmed the high safety of the biomaterial, regardless of storage period. The mean concentration of DNA was 69,96±6,56 ng/µl, extracellular DNA (ecDNA) — 0,20±0,02 ng/µl, ribonucleic acid — 38,16±5,69 ng/µl. DNA Integrity Number (DIN) >9, RNA integrity number (RIN) >7, A260/280 >1,8 were for all studied samples. Protein electrophoresis demonstrated no degradation of protein zones after longterm storage. The number of errors detected during the inventory was 84 (0,46% of all records in the database), while there were 64 donors with incomplete clinical information (15% of all donors in the collection).Conclusion. The necessity of mandatory implementation of standard operating procedures when creating and maintaining a collection, on the one hand, and periodic inventory with biosample quality assessment, on the other, has been demonstrated.